Pengaruh Reksadana Syariah, Saham Syariah, dan Inflasi terhadap Pertumbuhan Ekonomi Indonesia Tahun 2013-2022 - Maulidah Nur Qisti; Ahmad Budiman (Journal on Education, 2023)
The process of economic growth becomes an influence on people's welfare, and is also a benchmark for each country to see the growth and development of the country's economy in the long term. There are several factors that can affect the process of economic growth in Indonesia such as inflation and investment. Investment can encourage people to manage funds and provide income for the state. While good economic growth is having a stable inflation rate and increased investment. So that this study aims to examine how much influence Islamic mutual funds, Islamic stocks, and inflation have on Indonesia's economic growth in 2013-2022. As for this research, secondary data was collected through official websites, such as the Financial Services Authority (OJK) website for sharia mutual funds and sharia stocks, as well as the Central Bureau of Statistics (BPS) website for Indonesia's GDP economic growth and inflation. The population in this study are reports on Islamic mutual funds, Islamic stocks, inflation, and economic growth registered in 2013-2022. While the sample in this study used purposive sampling, which was taken from the entire quarter. To test the data used in this study, namely the multiple linear regression test, then the partial test (t test), simultaneous test (f test), and test the coefficient of determination (R2). Furthermore, from the results of the research conducted, it is known that partially Islamic mutual funds and Islamic stocks have a significant effect on economic growth, while partially inflation has no significant effect on economic growth. While simultaneously having a significant effect on Indonesia's economic growth.